The creator [videorecording (DVD)] - Edwards, Gareth, 1975-; Weitz, Chris, 1969-; Zimmer, Hans; Washington, John David, 1984-; Chan, Gemma, 1982-; Watanabe, Ken, 1959-; Simpson, Sturgill, 1978-; Chadha-Patel, Amar; Ineson, Ralph, 1969-; Ngo, Thanh Van, 1979-; Menchaca, Marc, 1975-; Voyles, Madeleine Yuna; et al. (20th Century Studios, 2023)
Amidst a future war between the human race and the forces of artificial intelligence, Joshua, a hardened ex-special forces agent grieving the disappearance of his wife, is recruited to hunt down and kill the Creator, the elusive architect of advanced AI who has developed a mysterious weapon with the power to end the war and mankind itself. Joshua and his team of elite operatives journey across enemy lines, into the dark heart of AI-occupied territory only to discover the world-ending weapon he's been instructed to destroy is an AI in the form of a young child.